Literature Review of Microcontroller-Based Automatic Power Factor Correction Systems and The Internet of Things - Gugut Hedi Afandi; Aji Brahma Nugroho; Iswahyudi (Universitas Muhammadiyah Surabaya, 2026)
Low power factors in industrial and household electrical systems cause energy waste, increased load flow, and financial losses due to fines for electricity providers. This systematic literature review aims to analyze the development, components, control methods, and performance achievements of microcontroller-based Automatic Power Factor Correction (APFC) systems and the Internet of Things (IoT) published in the period 2021–2026. The search was conducted through four scientific databases, namely Sage Journal, Scopus, Taylor & Francis, and IEEE Xplore, resulting in 108 initial articles that were then filtered using the PRISMA protocol until the final 10 articles were obtained. The results of the analysis show that the ESP32 and NodeMCU are the most commonly used microcontrollers, the PZEM-004T sensor as a power measuring tool, and the MQTT protocol as an efficient communication medium for real-time monitoring. The power factor improvement achieved ranges from 0.60–0.99 after the correction is applied. IoT integration has been shown to significantly improve remote monitoring and control capabilities.